Identification of Gold Sensing Peptide by Integrative Proteomics and a Bacterial Two-Component System - Ng, I-Son; Yu, You-Jin; Yi, Ying-Chen; Tan, Shih-I; Huang, Bo-Chuan; Han, Yin-Lung (Frontiers in Chemistry, 2017)
The proteomics strategy was utilized to analyze and identify the gold adsorption proteins from Tepidimonas fonticaldi AT-A2, due to its outstanding performance in gold-binding and recovery. The results showed that three small proteins, including histidine biosynthesis protein (HisIE), iron donor protein (CyaY) and hypothetical protein_65aa, have a higher ability to adsorb gold ions because of the negatively charged domains or metal binding sites. On the other hand, the Salmonella PmrA/PmrB two-component system first replaces the iron (III)-binding motif using the peptide sequence from hypothetical protein_65aa, and this is then used to reveal the sensing and responsiveness to gold metal ions, which is totally different from the performance of traditional gold binding peptide (GBP) on the crystals on the surface of gold (111). We have successfully demonstrated an integrative proteomics and bacterial two-component system to explore the novel gold binding peptide. Finally, the heterologous over-expression of gold binding peptide by E. coli and the equilibrium of binding capacity for Au(III) have been conducted.